Performance of CI Engine Operating with Hydrogen Supplement Cocombustion with Jojoba Methyl Ester - Hamdan, Mohammad O. (2016)
The present work experimentally investigates the performance of compression ignition (CI) engine which operates on hydrogen and Jojoba methyl ester (JME). The hydrogen is introduced by enriching air-intake manifold with hydrogen gaseous supplement at the atmospheric condition which is co-combusted in the presence of pilot flame that is initiated by jojoba methyl ester. The engine is supplied with a range of hydrogen-JME fuel mixture proportions to study the effect of hydrogen supplement on combustion and exhaust emissions. Under fixed flow rate of JME, the data shows that hydrogen supplement enhances diesel engine thermal efficiency while reducing specific fuel consumption. The gas emission results shows that as hydrogen supplement increases, NOx emission mildly increases while opacity majorly increases. Hydrogen supplement affects the internal combustion by causing an increase in internal pressure, pressure rise rate and maximum heat release rate. The experiment shows that hydrogen-JME duel fuel smoothly combust in compression ignition engine.